A sea surface temperature reconstruction for the southern Indian Ocean trade wind belt from corals in Rodrigues Island (19°S, 63°E) - Zinke, Jens; Reuning, L.; Pfeiffer, M.; Wassenburg, J.; Hardman, E.; Jhangeer-Khan, R.; Davies, G.; Ng, K.; Kroon, D. (Copernicus GmbH, 2016)
The western Indian Ocean has been warming rapidly over recent decades, causing a greater number of extreme climatic events. It is therefore of paramount importance to improve our understanding of links between Indian Ocean sea surface temperature (SST) variability, climate change and sustainability of tropical coral reef ecosystems. Here we present monthly resolved coral Sr∕Ca records from two different locations from Rodrigues Island (63° E, 19° S) in the south-central Indian Ocean trade wind belt. We reconstruct SST based on a linear relationship with the Sr∕Ca proxy with records starting from 1781 and 1945, respectively. We assess relationships between the observed long-term SST and climate fluctuations related to the El Niño–Southern Oscillation (ENSO), the Subtropical Indian Ocean Dipole Mode (SIOD) and the Pacific Decadal Oscillation (PDO) between 1945 and 2006, respectively. The reproducibility of the Sr∕Ca records is assessed as are the potential impacts of diagenesis and corallite orientation on Sr∕Ca–SST reconstructions. We calibrate individual robust Sr∕Ca records with in situ SST and various gridded SST products. The results show that the SST record from Cabri provides the first Indian Ocean coral proxy time series that records the SST signature of the PDO in the south-central Indian Ocean since 1945. We suggest that additional records from Rodrigues Island can provide excellent records of SST variations in the southern Indian Ocean trade wind belt to unravel teleconnections with the SIOD/ENSO/PDO on longer timescales.